Election Day : How We Vote and What It Means for Democracy - Chapman, Emilee (Book collections on Project MUSE., 2022)
"An original defense of the unique value of voting in a democracy. Voting is only one of the many ways that citizens can participate in public decision making, so why does it occupy such a central place in the democratic imagination? In Election Day, political theorist Emilee Booth Chapman provides an original answer to that question, showing precisely what is so special about how we vote in today's democracies. By presenting a holistic account of popular voting practices and where they fit into complex democratic systems, she defends popular attitudes toward voting against radical critics and offers much-needed guidance for voting reform. Elections embody a distinctive constellation of democratic values and perform essential functions in democratic communities. Election day dramatizes the nature of democracy as a collective and individual undertaking, makes equal citizenship and individual dignity concrete and transparent, and socializes citizens into their roles as equal political agents. Chapman shows that fully realizing these ends depends not only on the widespread opportunity to vote, but also on consistently high levels of actual turnout, and that citizens' experience of voting matters as much as the formal properties of a voting system. And these insights are also essential for crafting and evaluating electoral reform proposals.By rethinking what citizens experience when they go to the polls, Election Day recovers the full value of democratic voting today"--